Association of Procalcitonin With Acute Pyelonephritis and Renal Scars in Pediatric UTI - Leroy, Sandrine; Fernandez-Lopez, Anna; Nikfar, Roya; Romanello, Carla; Bouissou, Francois; Gervaix, Alain; Chalumeau, Martin (Amer Acad Pediatrics, 2013)
BACKGROUND AND OBJECTIVE: Urinary tract infections (UTIs) are common childhood bacterial infections that may involve renal parenchymal infection (acute pyelonephritis [APN]) followed by late scarring. Prompt, high-quality diagnosis of APN and later identification of children with scarring are important for preventing future complications. Examination via dimercaptosuccinic acid scanning is the current clinical gold standard but is not routinely performed. A more accessible assay could therefore prove useful. Our goal was to study procalcitonin as a predictor for both APN and scarring in children with UTI. METHODS: A systematic review and meta-analysis of individual patient data were performed; all data were gathered fromchildren with UTIs who had undergone both procalcitonin measurement and dimercaptosuccinic acid scanning. RESULTS: A total of 1011 patients (APN in 60.6%, late scarring in 25.7%) were included from 18 studies. Procalcitonin as a continuous, class, and binary variable was associated with APN and scarring (P < .001) and demonstrated a significantly higher (P < .05) area under the receiver operating characteristic curve than either C-reactive protein or white blood cell count for both pathologies. Procalcitonin >= 0.5 ng/mL yielded an adjusted odds ratio of 7.9 (95% confidence interval [CI]: 5.8-10.9) with 71% sensitivity (95% CI: 67-74) and 72% specificity (95% CI: 67-76) for APN. Procalcitonin >= 0.5 ng/mL was significantly associated with late scarring (adjusted odds ratio: 3.4 [95% CI: 2.1-5.7]) with 79% sensitivity (95% CI: 71-85) and 50% specificity (95% CI: 45-54). CONCLUSIONS: Procalcitonin was a more robust predictor compared with C-reactive protein or white blood cell count for selectively identifying children who had APN during the early stages of UTI, as well as those with late scarring.
Keywords: acute pyelonephritis; children; procalcitonin; renal scarring; urinary tract infection